Effect of alterations in whole-body cryotherapy (WBC) exposure on post-match recovery markers in elite Premier League soccer players - Malone, J. J.; Hodges, D.; Roberts, C.; Sinclair, K. J.; Page, M. R.; Allan, R. (Biology of Sport, 2022)
The use of whole-body cryotherapy (WBC) as a recovery intervention is prevalent amongst elite soccer players. However, there is a distinct lack of data available around chronic WBC use and post-match recovery markers in elite soccer. The aim of this study was to investigate the impact of different levels of WBC exposure on subjective and objective measures of post-match recovery in elite soccer players during a chronic exposure period. Sixteen male senior professional outfield soccer players participated in this study over two seasons. K means cluster analysis was used to classify low (-114 ± 2°C for 133 ± 2 s), medium (-121 ± 1°C for 173 ± 2 s) and high (-133 ± 1°C for 181 ± 2 s) cryotherapy exposure indexes (CEI). Salivary markers (immunoglobulin A (IgA) and alpha amylase (AA)) and subjective wellness scores (perceived fatigue, sleep quality, general muscle soreness and stress) were collected post-match across both seasons. Training load (session-RPE) was collected and used as a covariate to control for the load amongst groups. No differences were seen in perceived measures of wellness and salivary AA. Significantly lower IgA concentrations were observed in the medium CEI group (255 ± 32 µg·ml-1) compared to the low (328 ± 38 µg·ml-1) and high (306 ± 32 µg·ml-1) groups. Therefore, increasing the level of chronic WBC exposure appears to have no additional benefit on subjective recovery and alpha amylase response post-match. However, there appears to be an optimal chronic WBC dose with regards to IgA response.